A Socialist Feminist Reading of Thatcherite Women in British Feminist Plays - Berna Ayça Ülker Erkan (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This study focuses on the representation of women in British feminist drama that challenges gender roles and gets stuck in having obsessive power as an outcome of the policy of the first British woman Prime Minister Margaret Thatcher. The study discusses excessively ambitious women who question patriarchal order and subvert gender roles to get power and finally left alone on the top like Thatcher. Marlene in Caryl Churchill’s play Top Girls, Marion in Churchill’s play Owners, Mary Traverse in Timberlake Wertenbaker’s play The Grace of Mary Traverse are discussed throughly. Marlene, Marion, and Mary are the representatives of the destructive effects of the ambition for power that characterize Thatcher’s Britain. Socialist/materialist feminism is applied to the plays both to criticize selfish Thatcherite powerful women figures and to express the lack of collaboration among women to improve their position.